Initial value problem for fractional evolution equations - Fan, Hongxia; Mu, Jia (Advances in difference equations, 2012)
This article is concerned with the existence of mild solutions to the initial value problem for a class of semilinear evolution equations with fractional order. New existence theorems are obtained by means of fixed point theorem for condensing maps. The results extend some related results in this direction. Mathematics Subject Classification (2000) : 34A12; 35F25.